Conservative interventions and clinical outcome measures used in the perioperative rehabilitation of breast cancer patients undergoing mastectomy: a scoping review - Janny Mathieu; Catherine Daneau; Nadège Lemeunier; Annabelle Doyon; Andrée-Anne Marchand; Martin Descarreaux (BMC, 2022)
Abstract Background Mastectomy is the first-line treatment approach for more than 90% of breast cancer patients. The numerous physical impairments associated with this surgical procedure negatively impact the patient's quality of life. To date, rehabilitation resources available for breast cancer patients undergoing mastectomy within the institutions affiliated to the Centre intégré universitaire de soins de santé et de services sociaux de la Mauricie-et-du-Centre-du-Québec (CIUSSS-MCQ) are lacking and do not always seem to reflect the particularities of breast cancer care pathways. The purpose of this review was to identify and describe the conservative interventions and the clinical outcome measures used in the perioperative physical rehabilitation of women with breast cancer who are awaiting or have undergone mastectomy. We also aimed to report on the barriers and facilitators to study participation and completion. Methods MEDLINE, CINAHL, and the Cochrane Library were searched from inception to January 2021, and we updated the search on July 11, 2022. We included peer-reviewed English and French literature with quantitative designs, describing conservative interventions and clinical outcome measures used within rehabilitation programs designed for women who were awaiting or had undergone mastectomy. Paired reviewers independently reviewed all citations and articles using a two-phase screening process and independently extracted the data. Results Of the 6080 articles identified, 57 met the inclusion criteria. Most interventions were multimodal, which combined exercise with patient education, manual therapy, and/or lymphatic drainage. The most frequently used objective measures of physical function were shoulder range of motion, muscle strength, and signs of lymphedema. In contrast, the primary patient-reported outcome measures were quality of life, shoulder function, and pain. Undergoing another breast surgery, death, and cancer recurrence were the most reported barriers to study completion. Conclusion This scoping review reports on the heterogeneity and wide range of conservative interventions and clinical outcome measures used in the physical rehabilitation of breast cancer patients who had undergone or were scheduled to undergo mastectomy. Tailoring interventions to breast cancer patients' needs and promoting outpatient rehabilitation interventions appear to be better suited to the particularities of breast cancer care pathways. Further research is needed to better identify barriers and facilitators to study participation and completion.